Emulating an Ethereum Blockchain Network Using the LST - Azevedo, Andrei C.; Scheid, Eder J.; Franco, Muriel F.; Granville, Lisandro Z. (Anais da Escola Regional de Redes de Computadores (ERRC); 2023: Anais da XX Escola Regional de Redes de ComputadoresDO - 10.5753/errc.2023.918, 2023)
Besides the main blockchain use-case of exchanging cryptocurrencies, Distributed Applications (DApps) can also be developed on top of such a technology. However, due to the size of popular blockchains and price, testing these DApps in a real-world environment becomes challenging. Thus, blockchain emulators were proposed to address such as issue. This paper presents the experience of emulating an Ethereum network using a Docker-based lightweight testbed developed for Software Defined Networks (SDN).